Conference Report Inter-Religious Diplomacy in Asia: Preparing for a Papal Visit - Chia, Edmund (Archīum Ateneo, 2024)
This article is a report on a conference held in Singapore in anticipation of the visit of Pope Francis to Asia in September 2024. The conference was organized to address issues of inter-religious diplomacy, especially the role of the Vatican in Asia from a historical, sociological, political, religious, and theological perspectives. The first part of the article offers a glimpse of what some of the main presenters spoke on, in particular as they relate to the Catholic Church, and the second a summary of my own contribution which was on Confucian-Christian relations in Asia.